Efficacy of Artemether-Lumefantrine on various Plasmodium falciparum Kelch 13 and Pfmdr1 genes isolated in Ghana. (November 2020) - Aninagyei, Enoch; Tetteh, Comfort Dede; Oppong, Martin; Boye, Alex; Acheampong, Desmond Omane
Abstract: Introduction: Artemether-Lumefantrine (A-L) remains the drug of choice for the treatment of uncomplicated malaria in Ghana. However, the pharmaco-activity of A-L has not been assessed on various Plasmodium falciparum Kelch 13 and Pfmdr1 genes. Therefore, this study sought to determine the therapeutic efficacy of A-L on P. falciparum parasites isolated from Ghana. Methods: The clinical study was done in Ga West Municipality, Ghana, where 78 uncomplicated malaria patients were recruited with prior consent. The patients were treated orally with A-L according to national treatment guidelines. Baseline parasitaemia was determined before treatment and 8-hourly parasitaemia posttreatment were determined till initial clearance of parasitaemia and at days 7, 14, 21, and 28. Kelch 13 and Pfmdr1 genes were genotyped by sequencing using baseline samples. Parasite clearance characteristics were determined using Parasite Clearance Estimator beta 0.9 application. Results: Five Kelch 13 (F446I, S466N, R539I, A578S, and A676S) and three Pfmdr1 mutations (N86Y, Y184F and D1246Y) were identified in 78 infected samples. About 8% of the samples contained two Pfmdr1 double mutations (N86Y & D1246Y and Y184F & N86Y). Additionally, three samples (3.8%) were found to contain both Kelch 13 mutations and Pfmdr1 wild type genes. In all patients, parasitaemia persisted within the first 24 h of A-L therapy. However, at hour 40, only two patients were parasitaemic while all patients were aparasitaemic at hour 48. The genotypic profiles of the two persistent parasites at hour 40 were F446I and D1246Y, and R539I, Y184F, and N86Y. The slope half-life of the former was 6.4 h while the latter was 6.9 h and their respective PCT99 were 47.9 h and 49.2 h as well as a clearance rate constants of 0.109 and 0.092 respectively. Conclusion: This study reports the effectiveness of A-L on various P. falciparum mutant alleles. However, continuous surveillance of Kelch 13 mutations and Pfmdr1 gene in Ghana and regular assessment of the therapeutic efficacy of A-L and other artemisinin derivatives is recommended.